BERAT BADAN LAHIR DENGAN ROBEKAN PERINEUM PERSALINAN NORMAL PADA PRIMIGRAVIDA - Subriah, Subriah; Husain, Hastuti; Nurjaya, Nurjaya (Politeknik Kesehatan Makassar, 2022)
ABSTRACT In health care facilities, rupture perineal still occurs even though the baby is not born too big, either spontaneous rupture or rupture on purpose (episiotomy). According to APN clinical training, 2008 spontaneous rupture of the vagina or perineal can occur at the time the head and shoulders are born. This study used a correlation analytic method with a cross sectional design. The population in this study were all women who gave birth at the Kassi-Kassi Public Health Center in Makassar City. Using the formula, a Lemeshow total sample of 30 people was obtained with a sampling technique, namely consecutive sampling. The results of the research Fisher's Exact Test with value p= 0,019, the probability result is smaller than the significant level of 5% (0.019<0.05), meaning that there is a relationship between birth weight and tears perineal normal labor in primigravidas at Kassi-Kassi Public Health Center Makassar City in 2020 the strength of the relationship between variables is rather low, the coefficient of Phi (μ) = 0,488 or 48,8%. Therefore, it is recommended for pregnant women, especially mothers, to primigravida do pregnancy exercises in the third trimester so that they have perineal an elastic to reduce the risk of rupture perineal spontaneous, consume foods that contain lots of fiber, low carbohydrates and high protein, avoid stress and fatigue before childbirth. To prevent the occurrence of prolonged labor or labor jams. For health workers, it can increase education to pregnant women about the factors that affect perineal rupture so that at the time of delivery the incidence of perineal rupture can be reduced and the rate of perineal rupture can be minimized. In addition, it is hoped that it can increase awareness in providing delivery assistance so that perineal rupture does not occur and is expected to be able to provide IEC to pregnant women regarding the weight of newborns. Keywords: Birth Weight, Normal Labor, Primigravida, Perineal Tearing. ABSTRAK Pada sarana pelayanan kesehatan, ruptur perineum masih terjadi meskipun bayi yang di lahirkan tidak terlalu besar, baik itu ruptur spontan maupun ruptur yang disengaja (episiotomi). Menurut pelatihan klinik APN, 2008 ruptur spontan pada vagina atau perineum dapat terjadi pada saat kepala dan bahu dilahirkan.Penelitian ini menggunakan metode analitik korelasi dengan rancangan potong silang atau cross sectional. Populasi dalam penelitian ini adalah semua ibu bersalin yang ada di Puskesmas Kassi-Kassi Kota Makassar, menggunakan rumus Lemeshow didapatkan jumlah sampel 30 orang dengan teknik pengambilan sampel yaitu consecutive sampling.Hasil penelitian Uji Fisher’s Exact Test dengan nilai p=0,019, hasil probabilitas lebih kecil dari taraf signifikan 5% (0,019<0,05) artinya ada hubungan berat badan lahir dengan robekan perineum persalinan normal pada primigravida di Puskesmas Kassi-Kassi Kota Makassar tahun 2020. Kekuatan hubungan antarvariabel agak rendah diperoleh nilai koefisien Phi (μ)= 0,488 atau sebesar 48,8%.Oleh karena itu, disarankan bagi ibu hamil terutama ibu primigravida hendaknya melakukan senam hamil pada trimester III agar mempunyai perineum yang elastis untuk mengurangi risiko terjadinya ruptur perineum spontan, mengkonsumsi makanan yang banyak mengandung serat, rendah karbohidrat dan tinggi protein, menghindari stres dan kelelahan menjelang persalinan untuk mencegah terjadinya partus lama atau partus macet. Bagi tenaga kesehatan dapat meningkatkan penyuluhan terhadap ibu hamil tentang faktor-faktor yang mempengaruhi ruptur perineum sehingga pada saat persalinan kejadian ruptur perineum dapat dikurangi dan tingkat ruptur perineum dapat diminimalkan. Selain itu, diharapkan dapat lebih meningkatkan kewaspadaan dalam melakukan pertolongan persalinan sehingga tidak terjadi ruptur perineum serta diharapkan mampu memberikan KIE kepada ibu hamil mengenai berat badan bayi baru lahir. Kata Kunci: Berat Badan Lahir, Persalinan Normal, Primigravida, Robekan Perineum.